Guest workers: herders, borregueros or peões in the United States and Canada rocky mountains - Stein, Leila de Menezes; Coutinho, Beatriz Isola (Universidade Estadual de Campinas, UNICAMP, Unidade da Faculdade de Ciências Aplicadas de Limeira-SP, vinculada ao Laboratório de Estudos do Setor Público, LESP, 2013)
In the contemporary world and in the globalized farm labor market, employ temporary immigrants workforce become current in economic developed countries. With governmental support, nations as United States and Canada incite and lawful the foreign entrance for occupy jobs and functions that are not fulfilling by native born, consolidating the displacement of a cheap labor force that stays legally for a certain season in these countries. This article brings up primal subjects about a small and hidden group among farm immigrants, the herders, sheepherders and goat herders in north- America Rocky Mountains loneliness. Further to provide an initial theoretical instrumental for the reflections about these workers, we intend to localize them within migration theme and the conflict between capital and labor in these days, in its neoliberal context and struggle forms. For such, we used reflections about labor and migration, also different kind of documents about herders in both countries.